Trade and sustainable development: regulating PPMs in the WTO - Jere, Maude (Department of Commercial Law, 2017)
The popularisation of sustainable development and increasing alarm of the over-exploitation of natural resources and its impact on the environment has forced the international community to recognise that the current condition of the environment is a global concern. Developing alongside this recognition is an awareness of the relationship between economic growth/ trade liberalisation and the environment. The reconciliation of trade and environment necessarily involves international trade organisations and how their policies affect the environment. To this end a large part of the trade and environment debate has involved the World Trade Organisation (WTO) and its approach to trade measures that relate to environmental protection, more specifically, on whether its treatment of non-product related Process and Production Methods is in line with the goal of sustainable development. In a setting where the 'the major cause of the continued deterioration of the global environment is the unsustainable pattern of consumption and production', states have been charged with the responsibility of setting standards that regulate the processes and methods used to produce goods so that the damage to the environment is minimised. Has the WTO been able to balance the goal of trade liberalisation with environmental protection and does its policy in relation to non-product-related Process and Production Methods undermine sustainable development and the ability of states to set their own environmental protection agenda? The dissertation will try to show that while GATT rules are not designed to undermine the objective of environmental protection, their application has reduced the ability of states to set their own agendas in relation to environmental protection. This will be done through an examination of case law with reference to the 'like product' analysis under Article III of the GATT which governs domestic regulations and the treatment they afford to domestic and imported products. It will show that the WTO's reluctance to use non-product related Process and Production Methods as a way of differentiating products, has the potential of undermining the efficacy of ecological protections put in place in pursuit of sustainable development. After an examination of Article XX, the thesis shows that while Article XX provides exceptions to the obligations of member states, it does not provide enough stability and predictability to address the failing of Article III. In doing the WTO has hindered the promotion of sustainable development as PPMs which are largely a response to failed multilateral efforts to achieve consensus on environmental protection.